Health Information Research Platform (HIReP): an architecture pattern - Schreiweis, Björn; Schneider, Gerd; Eichner, Theresia; Bergh, Björn; Heinze, Oliver (E-Health - for continuity of care, 2014)
Secondary use or single source is still far from routine in healthcare, although lots of data are available either structured or unstructured. As data are stored in multiple systems, using them for biomedical research is difficult. Clinical data warehouses already help overcoming this issue, but currently they are only used for certain parts of biomedical research. A comprehensive research platform based on a generic architecture pattern could increase the benefits of existing data warehouses for both patient care and research by meeting two objectives: serving as a so called single point-of-truth and acting as a mediator between them strengthening interaction and close collaboration. Another effect is to reduce boundaries for the implementation of data warehouses. Taking further settings into account the architecture of a clinical data warehouse supporting patient care and biomedical research needs to be integrated with biomaterial banks and other sources. This work provides a solution conceptualizing a comprehensive architecture pattern of a Health Information Research Platform (HIReP) derived from use cases of the patient care and biomedical research domain. It serves as single IT infrastructure providing solutions for any type of use case.
Gesehen am 15.02.2021